2014
DOI: 10.1038/mp.2014.22
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic differences in hiPSC NPCs derived from patients with schizophrenia

Abstract: Consistent with recent reports indicating that neurons differentiated in vitro from human induced pluripotent stem cells (hiPSCs) are immature relative to those in the human brain (1, 2), gene expression comparisons of our hiPSC-derived neurons to the Allen BrainSpan Atlas indicate that they most resemble fetal brain tissue. This finding suggests that, rather than modeling the late features of schizophrenia (SZ), hiPSC-based models may be better suited for the study of disease predisposition. We now report tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
392
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 375 publications
(425 citation statements)
references
References 32 publications
30
392
3
Order By: Relevance
“…Though NPCs appear to be morphologically similar by eye, they are a heterogeneous population comprised of cells capable of generating both glutamatergic and GABAergic neurons. While we observe remarkably consistent forebrain patterning of NPC lines between individuals using this method 1 , this is only when comparing fully validated high quality NPC lines -there are substantial differences between good and poor quality NPC lines. Additionally, viral transduction yields genetically heterogeneous cells, each with an integration of the viral vector at a unique genomic location; therefore, individual cells will vary both in the location and number of genomic integration sites.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Though NPCs appear to be morphologically similar by eye, they are a heterogeneous population comprised of cells capable of generating both glutamatergic and GABAergic neurons. While we observe remarkably consistent forebrain patterning of NPC lines between individuals using this method 1 , this is only when comparing fully validated high quality NPC lines -there are substantial differences between good and poor quality NPC lines. Additionally, viral transduction yields genetically heterogeneous cells, each with an integration of the viral vector at a unique genomic location; therefore, individual cells will vary both in the location and number of genomic integration sites.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, because one can rapidly generate large numbers of cells and need not wait weeks or months for neuronal maturation, NPC-based assays are suitable for the study of larger patient cohorts and are more amenable to high throughput screening. We believe that hiPSC NPCs can serve as a proxy for the developmental pathways potentially contributing to disease pathogenesis, as has already been demonstrated in disorders as diverse as schizophrenia 1 and Huntington's disease 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct reprogramming of somatic cells into a target cell type by forced expression of reprogramming factors without going through an intermediate iPS cell state is a very powerful tool for disease modelling because of the ability to generate specific mature human somatic cells within a short period of time. Our laboratory has demonstrated that fibroblasts could be directly converted into functional mature neuronal cells within two weeks, whereas conventional differentiation of pluripotent cells into somatic lineages (such as neural, hematopoietic, cardiac and hepatic) through exposure to morphogens and small molecules produces cells that are typically immature, resembling fetal stages [72]. Even maturation times of several months are often insufficient to generate mature, adult-like cell types from pluripotent stem cells.…”
Section: Direct Conversion Of Somatic Cells Versus Induction Of Plurimentioning
confidence: 99%